Brief Report: Monoclonal Gammopathy and Risk of Lymphoma and Multiple Myeloma in Patients With Primary Sjögren's Syndrome. Issue 5 (27th April 2016) - Tomi, Anne‐Laurence; Belkhir, Rakiba; Nocturne, Gaétane; Desmoulins, Frédéric; Berge, Elisabeth; Pavy, Stephan; Miceli‐Richard, Corinne; Mariette, Xavier; Seror, Raphaèle
Abstract : Objective: To assess the link between monoclonal gammopathy (MG), disease activity, and incidence of malignant hematologic disorders (MHDs), including lymphoma and multiple myeloma (MM), in patients with primary Sjögren's syndrome (SS). Methods: Screening for the presence of MG was performed in 352 primary SS patients. Each patient with MG was paired with 2 age‐ and sex‐matched primary SS controls without MG. Their characteristics were compared for the presence of risk factors for MG and for the relationship between MG and MHD. Results: Twenty‐six of the 352 primary SS patients (7.4%) had MG; 88% were women, with a median age of 62.7 years (interquartile range [IQR] 50.3–69.1 years) and a median disease duration of 7.8 years (IQR 3.6–12.8 years). The parameters associated with MG on multivariate analysis were higher disease activity, as measured by either the European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (ESSDAI; adjusted odds ratio [OR] 9.7, P  = 0.0002) or the Clinical ESSDAI (adjusted OR 6.7, P  = 0.001), and low C4 level (adjusted OR 3.4, P  = 0.04). After a median follow‐up of 6.3 years (IQR 3.1–9.5 years), 10 patients with MG had developed an MHD (38.5%; 4 had lymphomas and 6 had MM), as compared with 4 patients in the control group (7.7%; all had lymphomas) (OR 7.5, P  = 0.002). The only factor associated with the risk of MHDs was the presence of MG (adjusted OR 5.5, P  = 0.02), which was principally associated with an increased risk of MM (23% versus 0%; P  = 0.0009), but not lymphoma (15% versus 8%; P  = 0.3). Conclusion: The presence of MG was associated with higher disease activity and an increased risk of MHD in primary SS. In the presence of MG, the risk of MM was even higher than the risk of lymphoma. These results suggest that regular monitoring of primary SS patients with MG for the emergence of both lymphoma and MM is necessary.